2021
DOI: 10.1039/d1sm00311a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic underpinning of cell aspect ratio-dependent emergent collective motions in swarming bacteria

Abstract: Self-propelled bacteria can exhibit a large variety of non-equilibrium self-organized phenomena. Swarming is one such fascinating dynamical scenario where a number of motile individuals group into dynamical clusters and move...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…For instance, Mitchell (36) calculated that a change in cell diameter of only 0.2 μm can escalate the energy required for chemotaxis by a factor of 10 5 . Cell aspect ratio also seems to play an important role in determining the amount of drag a cell is subject to during motion (37). Our COMSOL numerical simulation is corroborated by the findings presented in other studies (38, 39) where it was demonstrated that drag forces are generally higher for spherocylinders than for spheroid-shaped objects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Mitchell (36) calculated that a change in cell diameter of only 0.2 μm can escalate the energy required for chemotaxis by a factor of 10 5 . Cell aspect ratio also seems to play an important role in determining the amount of drag a cell is subject to during motion (37). Our COMSOL numerical simulation is corroborated by the findings presented in other studies (38, 39) where it was demonstrated that drag forces are generally higher for spherocylinders than for spheroid-shaped objects.…”
Section: Discussionmentioning
confidence: 99%
“…23,33 The repulsive force has been modeled by the expression: F rf = Ed 1/2 0 h 3/2 , where E is the elastic modulus of the cells and h = d 0 − r represents the overlap between two interacting cells, where r corresponds to the closest distance of the approach between the two cells. 7,8,22,23,33,34,44 Similarly, a cell and EPS particle will experience repulsive mechanical force if the closest distance of approach between them is lesser than the sum of the radii of the cell and the EPS particle. However, in our model, to mimic the sticky nature of the EPS to the cell surface, we have introduced a short-range attractive force ( F af ) between them.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Here, r corresponds to the closest distance of approach between two particles. 15,19,[23][24][25]60 Besides these, each particle experiences a random force, z, from the surrounding medium, which stems from a uniform distribution with the range from À10 À3 to +10 À3 . 15,26 The persistence of bacteria is profoundly influenced by a complex interplay of numerous contributing factors, such as cell division, repulsive force (F rf ) and torque acting on the bacteria.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Bacteria are a well-known example of living active matter that exhibit a variety of complex morphodynamics in their lifestyles. They can show a broad spectrum of nonequilibrium collective phenomena, such as patterned colonies, [1][2][3][4][5][6][7] biofilm formation, [8][9][10][11][12][13][14][15][16] swarming, and turbulent motions, [17][18][19][20][21] depending on the species and environmental conditions. The interplay of growth, division, motions, and local interactions of individual components plays a crucial role in controlling such phenomena.…”
Section: Introductionmentioning
confidence: 99%